PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI ANDROID UNTUK MENINGKATKAN HASIL BELAJAR KEWIRAUSAHAAN (Studi Pada Kelas XI APK SMK Muhammadiyah 3 Singosari Materi Aspek Organisasi) - Muhammad Fahmi Tri Kurniawan; Lisa Rokhmani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
The purpose of this research is produced interactive learning media used for android which will be used for students class XI APK SMK Muhammadiyah 3 Singosari aspecially on the subject of entrepreneurship Lesson. Design in this research 4D model (Four D). The stages to be performed by the researcher include 1) Define, 2) Design, 3) Development, and 4) Disseminate. In these stages will be validated by a team of experts consisting of expert material, expert media, and trial to explore the effectiveness of the product developed. On the results of the validity of experts material obtained results 72.87%, quite valid, on the sheet of validity expert media obtained results 91.25%. In the user trial obtained the results of 83.42% and applies to the average overall repetition rate was found at 82.51% which can be concluded that the learning media based on android application on the Entrepreneurship lessons is valid and feasible to used.